The Effects of Mobile Banking Service Quality on The Satisfaction of The Customers of Bank Central Asia (BCA) - Nuraini, Karina Ayu; Ashar, Khusnul (Contemporary Studies in Economic, Finance and Banking, 2025)
The rapid advancement of technology creates the need for agencies to increase innovation in accordance with the needs of the times. One of the innovations made by banks is by launching mobile banking applications. With mobile banking, it is expected to increase customer satisfaction. This study aims to analyze the effect of mobile banking service quality on the satisfaction of the customer of Bank Central Asia (BCA). Mobile banking service quality is measured through four variables, namely speed (X1), security (X2), accuracy (X3) and trust (X4). The theory used in this research is the Technology Acceptance Model (TAM) theory. The results showed that two variables of mobile banking service quality, namely accuracy and trust, had a positive effect on BCA bank customer satisfaction. This indicates that customers highly value the accuracy of information and transactions, and have high trust in BCA bank mobile banking services, which will increase customer satisfaction.